THE IMPORTANCE OF THE CLINICAL PICTURE AND DEVELOPMENT OF THE CONDITION OF PERIODONT TISSUE DISEASES IN PREGNANT WOMEN - Jasur A. Rizaev; Elbek R. Vohidov; Nodira Sh. Nazarova (Central Asian Journal of Medicine, 2024)
Pregnant women have the highest risk of dental diseases. According to a number of authors, the prevalence of dental caries during the physiological period of pregnancy is 91.4%, in 90% of cases, diseases of the periodontal disease tissue, mainly damage to healthy teeth with an acute course of the carious process, make up 38% of pregnant women. Secondary caries, development of the caries process, enamel hyperesthesia in 79% of pregnant women. At the same time, the growth intensity of dental caries in terms of the absolute increase in the index of caries-fillers-removed teeth during pregnancy is 0.83.